Robo Sapiens Bankerius: An Ideally Designed Humanoid Banking Service Robot? - Alexandra Prisznyák (Financial and Economic Review)
Autonomous intelligent robots are playing an increasingly prominent role in the banking sector. The acceptance and perception of these robots as social actors depends on various factors. Through the process of anthropomorphisation, people attribute human-like characteristics, behavioural patterns or intentions to robots. This essay explores the anthropomorphisation of banking robots and examines the interactions between key robot features: social skills, functionality and appearance. It presents the theoretical concept of an ideally designed “Robo Sapiens Bankerius”. A questionnaire-based survey involving 26 robots which focused on the evaluation of the anthropomorphic appearance of banking robots was conducted between 2023 and March 2025: it found that majority of respondents preferred less human-like robots. Age, gender, concerns and attitudes showed no significant correlation with the choice of robot. The analysis of the open-ended responses revealed trade-offs between robots' social capabilities, functionality, and appearance. These findings point to new directions for research and provide an opportunity to compare the results with international literature.